Respuesta :
[tex]\huge\text{Hey there!}[/tex]
[tex]\huge\textbf{Question reads....}[/tex]
[tex]\large\text{Which expression is equivalent to 2(x - 1) + x?}[/tex]
[tex]\huge\textbf{Step by step to find your result}[/tex]
[tex]\large\textbf{First you have to DISTRIBUTE 2 WITHIN the}\\\large\textbf{PARENTHESES}[/tex]
[tex]\large\text{2(x - 1) + x}\\\rightarrow\large\text{2(x) + 2(-1) + x}\\\rightarrow\large\text{2x - 2 + x}\\\rightarrow\large\text{2x - 2 + 1x}\\\rightarrow\large\textbf{COMBINE the LIKE TERMS}\leftarrow\\\rightarrow\large\text{(2x + 1x) - (2)}\\\rightarrow\large\text{3x - 2}[/tex]
[tex]\huge\textbf{FINALLY WE HAVE YOUR RESULT}[/tex]
[tex]\huge\boxed{\textsf{Therefore, your answer is: }}}\\\huge\boxed{\mathsf{Option\ B. \ 3x - 2}}\huge\checkmark[/tex]
[tex]\huge\text{Good luck on your assignment \& enjoy }\\\huge\text{your day!}[/tex]
~[tex]\frak{Amphitrite1040:)}[/tex]
Answer:
- Option B
Step-by-step explanation:
First, let's simplify the given expression.
- => 2(x - 1) + x
- => 2x - 2 + x
- => (2x + x) - 2
- => 3x - 2
Looking at all the options, we can say that Option B is correct.